Four-Network Integration in the Highway Infrastructure Field of China - Chunfang Lu; Mengyong Weng; Fei Liu; Hucheng Sun; Zhenru Fu; Jing Sun (中国工程科学)
Considering the rapid development of information and communication technologies as well as the transformation of the energy industry, it is necessary to integrate the transportation infrastructure with the transport service, information, and energy sectors, thereby enhancing the service capabilities of the transportation system and promoting technological innovation and high-quality development of the comprehensive transportation infrastructure. Focusing on boosting China's strength in transportation, this study clarifies the definition and characteristics of four-network integration (i.e., integration of the transportation infrastructure, transport service, information, and energy networks), and reviews the practical basis for improving the efficiency of the highway infrastructure from energy, information, service and other aspects. Moreover, it analyzes the development status and existing problems regarding four-network integration in the highway infrastructure field of China, and proposes the general idea, goals, system framework, and development modes of four-network integration in the field. Key tasks include building a new infrastructure system based on four-network integration, establishing a stable and reliable energy supply system for the highway infrastructure, upgrading the information service system, and building a multi-industry integrated service system for four-network integration. Furthermore, the study suggests the establishment of a management mechanism in line with the characteristics of four-network integration, a guidance mechanism in line with the application characteristics of new technologies, a sound standards and specification system for four-network integration, and an implementation monitoring, evaluation, and cooperation mechanism.